2019
DOI: 10.1016/j.molp.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Wx, the Ancestral Allele of Rice Waxy Gene

Abstract: In rice grains, the Waxy (Wx) gene is responsible for the synthesis of amylose, the most important determinant for eating and cooking quality. The effects of several Wx alleles on amylose content and the taste of cooked rice have been elucidated. However, the relationship between artificial selection and the evolution of various Wx alleles as well as their distribution remain unclear. Here we report the identification of an ancestral allele, Wx lv , which dramatically affects the mouthfeel of rice grains by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 56 publications
4
130
0
Order By: Relevance
“…2). Amylose-free varieties of crops have been cultivated for centuries, but these mutants have been maintained in several crop species by positive selection for the desirable properties of amylose-free starch and flour (Olsen and Purugganan, 2002;Stamp et al, 2016;Zhang et al, 2019). Thus, the discovery of wild accessions of a noncultivated plant species that contain no or very low amylose is surprising.…”
Section: Intraspecies Diversity In Amylose Content In Arabidopsismentioning
confidence: 99%
“…2). Amylose-free varieties of crops have been cultivated for centuries, but these mutants have been maintained in several crop species by positive selection for the desirable properties of amylose-free starch and flour (Olsen and Purugganan, 2002;Stamp et al, 2016;Zhang et al, 2019). Thus, the discovery of wild accessions of a noncultivated plant species that contain no or very low amylose is surprising.…”
Section: Intraspecies Diversity In Amylose Content In Arabidopsismentioning
confidence: 99%
“…For example, in rice, the Waxy (Wx) gene encodes a granule-bound starch synthase, which regulates the amylose content and determines the eating and cooking quality [44]. In indica rice that contains high endosperm amylose level, Wx with a normal sequence has correct mRNA transcripts, whereas the Wx in japonica rice shows a single base change at the 5 splice site (splice donor site) of the first intron, representing a larger mRNA with retention of the first intron, which reduces the levels of Wx protein and endosperm amylose [44][45][46]. A mutation at the 3 splice site (splice acceptor site) of a intron in MUTANT snc1-ENHANCING (MUSE), an Arabidopsis RNA polymerase III subunit, gives rise to intronic retention and partial loss-of-function of MUSE, leading to pleiotropic defects in vegetative development [47].…”
Section: Introductionmentioning
confidence: 99%
“…In rice, the Waxy (Wx) gene encoding GBSSI (granule-bound starch synthase I) controls amylose synthesis in endosperm and is the primary factor influencing grain eating and cooking quality (ECQ) (Sano, 1984;Tian et al, 2009). The natural allelic variations within the Wx locus are the main cause of the broad diversity of amylose content (AC) and ECQ in modern rice (Zhang et al, 2019). Our recent study revealed a high-to-low AC selection trend globally in the course of rice domestication (Zhang et al, 2019).…”
mentioning
confidence: 99%
“…The natural allelic variations within the Wx locus are the main cause of the broad diversity of amylose content (AC) and ECQ in modern rice (Zhang et al, 2019). Our recent study revealed a high-to-low AC selection trend globally in the course of rice domestication (Zhang et al, 2019). In recent decades, there have been advances in modulating AC and improving ECQ in both indica and japonica rice using certain Wx alleles, particularly Wx b and Wx in with low-tointermediate AC (Lau et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation